Scaling antimicrobial resistance surveillance nationally: The case of the Fleming Fund in Kenya - Kasudi, Mitchelle R.; Muloi, Dishon M.; Murungi, Maurice K.; Azegele, A.; Ndanyi, R.; Gunturu, R.; Ombajo, L.; Tanui, E.; Onsare, R.S.; Omuse, G.; Kariuki, S.; Fèvre, Eric M. (CAB International, 2024)
Rising levels of antimicrobial resistance (AMR) in both humans and animals have reached alarming levels and are being recognized as a serious incremental threat to global food security, animal health and public health. The One Health approach recognizes the interconnectedness of human, animal and environmental health, and that AMR can be spread between different species and environments. The Fleming Fund, a UK Overseas Development Aid program managed by the UK’s Department of Health and Social Care, aims to improve AMR and antimicrobial use (AMU) surveillance data in Africa and Asia by generating, sharing, and using data to improve antimicrobial use and encourage investment in AMR research and development. The Fund awarded grants to several countries, including Kenya, to support national efforts in strengthening their capacity to collect, manage and use data on antimicrobial use and resistance. Six institutions, including the International Livestock Research Institute, University of Nairobi, the Aga Khan University, the Kenya Medical Research Institute, PATH and Washington State University, formed the Fleming Fund consortium in Kenya. Across animal and human health sectors, this consortium supported activities that address the gaps in the surveillance of AMR and its causes including antimicrobial stewardship training, development and dissemination of standard operating procedures for both active and passive AMR surveillance, capacity building of field and laboratory personnel and infrastructure work among other activities. The wide range of data acquired through this program will impact evidence-based policies and programs, enabling consumers and stakeholders to make informed decisions that preserve the effectiveness of antibiotics.